Implementation of The New Student Admission Policy (PPDB) at the Elementary School Level in Denpasar City - Michael Josafat Prihanto (Eduvest - Journal of Universal Studies, 2025)
This study aims to evaluate the implementation of the New Student Admission (PPDB) policy at the elementary school level in Denpasar City. The results show that the implementation of PPDB is not optimal, influenced by two main factors: the content of the policy and the implementation environment. Although the government has designed policies involving various elements, the capacity of primary schools is insufficient to accommodate the enthusiasm of parents. In addition, social factors and compliance of implementers are also challenges in the implementation of policies. This research is expected to provide recommendations for policy makers to increase the effectiveness of PPDB in the future.